Optimal placement of distributed generation and capacitor in distribution system for district hospital in Malaysia. - Sharul Anuar, Maizatul Shafiqah (2023)
Recent advancements in power generation technologies using renewable energy resources and government policies toward a more sustainable future have called for environmental incentive. As a result, the application of renewable-based distributed generation in a distribution system has gained significant recognition due to its technical and environmental benefits. In this paper, Artificial Bee Colony (ABC) algorithm will be used to obtain optimal location and sizing of distributed generation (DG) and capacitor with power loss reduction as its main objective function. Four different cases were simulated to observe the effectiveness of both DG and capacitor in reducing the power loss when it was installed together. The simulated result showed that installing both DG and capacitors gave this study the best results and objective function, reducing power loss.